Transatlantic Miscommunication in David Hare’s Drama Stuff Happens“ - Golimowska, Karolina (Current Objectives of Postgraduate American Studies, 2012)
This article addresses the transatlantic relations between the United States and Europe and specifically Great Britain in the context of post-9/11 international politics as reflected in the drama Stuff Happens“ (2004) written by British playwright David Hare. It focuses on the way recent history is performed and contextualized in dramatic form and analyzes the function and power of the theatricalization“ of historic events and particularly of finding ways to address 9/11 on a stage. Furthermore, it discusses the method of mixing parts of public speeches quoted verbatim with fiction and its effects on readers and audiences. The play addresses the struggles and fragility of international diplomacy in the aftermath of 9/11. It reflects a general skepticism towards politicians and their decisions as well as the helpless position of millions of observers who are affected by these decisions and yet feel like they have no influence. This article sees post-9/11 verbatim theater as a chance for playwright and spectators to get access to the world of politics and to take part in the process of writing transatlantic history. More generally, through the example of this play, the article aims at discussing new challenges and functions of post-9/11 theater.